Temporary cross-clamping of the infrarenal abdominal aorta during cesarean hysterectomy to control operative blood loss in placenta previa increta/percreta - Min-Min, Chou; You-Min, Ke; Huey-Chun, Wu; Ching-Pei, Tsai; Esther, Shih-Chu Ho; Ismail, Hamizah; Jaraquemada, Jose M. Palacios (Elsevier, 2010)
Objective To evaluate the efficacy and safety of temporary cross-clamping of the infrarenal abdominal aorta for controlling operative blood loss during cesarean hysterectomy in severe invasive placentation.